1994
DOI: 10.1055/s-2006-959429
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofNardostachys jatamansion Biogenic Amines and Inhibitory Amino Acids in the Rat Brain

Abstract: Nardostachys jatamansi (Jones) DC. (Valerianaceae) is used in large quantities in the preparation of Ayurvedic and Unani drugs (1, 2). The decoction of the roots of this plant have been used for centuries in Ayurveda for epilepsy, hysteria, syncope, and mental weakness (3). Gupta et al. (4) reported that the ethanolic extract was found to be the most active and abolished the tonic extensor response in 50% of rats subjected to maximal electroshock seizures (MES). Jatamansone was found to be more effective than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…Jatamansone may enhance the effect of the neurotransmitter gamma-aminobutyric acid (GABA) at the GABAA receptor. 12 Jatamansi also contains alkaloids, Spirojatamol, Valerenic acid, Virolin and is having actions like sedative, hypotensive, anti-inflammatory, anti-stress, CNS depressant, anti-anxiety and analgesic activities.…”
Section: Discussionmentioning
confidence: 99%
“…Jatamansone may enhance the effect of the neurotransmitter gamma-aminobutyric acid (GABA) at the GABAA receptor. 12 Jatamansi also contains alkaloids, Spirojatamol, Valerenic acid, Virolin and is having actions like sedative, hypotensive, anti-inflammatory, anti-stress, CNS depressant, anti-anxiety and analgesic activities.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has clearly shown that nardostachys jatamansi has an influence on the excitatory and inhibitory neurotransmission, of special interest being the increase in the gamma amino butyric acid (GABA) levels. 17 Further study is required to confirm and isolate the active principle/principles that contributes to the anticonvulsant activity. The active principle/principles when isolated may prove to be a prospective broad spectrum anticonvulsant agent, either alone or in combination with already available anticonvulsant drugs.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 N. jatamansi has also been reported to enhance biogenic amine activity, 48 decrease the level of dopamine and its metabolites and increasing the number of dopaminergic D2 receptors in striatum. 29 Such evidence supports our study and indicates that the extract of N. jatamansi inhibits the symptoms of haloperidol-induced catalepsy in rats.…”
Section: Discussionmentioning
confidence: 99%